Unforgettable experience in China - Siti Sarah, Mohamad Rajimi (2017)
Fahmi Muhammad Rasyid Rabuan, 2nd year UMP student from Faculty of Chemical & Natural Resources Engineering (FKKSA) won 2nd place in China Bridge Competition while 1st place goes to Muhamad Shahmeer Mohd Nashrul from Universiti Teknologi MARA (UiTM).